Assessing the Biocompatibility of Multi-Anchored Glycoconjugate Functionalized Iron Oxide Nanoparticles in a Normal Human Colon Cell Line CCD-18Co - Raval, Yash S.; Samstag, Anna; Taylor, Cedric; Huang, Guohui; Mefford, Olin Thompson; Tzeng, Tzuen-Rong Jeremy (Nanomaterials (Basel, Switzerland), 2021)
We have previously demonstrated that iron oxide nanoparticles with dopamine-anchored heterobifunctional polyethylene oxide (PEO) polymer, namely PEO-IONPs, and bio-functionalized with sialic-acid specific glycoconjugate moiety (Neu5Ac(α2-3)Gal(β1-4)-Glcβ-sp), namely GM3-IONPs, can be effectively used as antibacterial agents against target Escherichia coli. In this study, we evaluated the biocompatibility of PEO-IONPs and GM3-IONPs in a normal human colon cell line CCD-18Co via measuring cell proliferation, membrane integrity, and intracellular adenosine triphosphate (ATP), glutathione GSH, dihydrorhodamine (DHR) 123, and caspase 3/7 levels. PEO-IONPs caused a significant decrease in cell viability at concentrations above 100 μg/mL whereas GM3-IONPs did not cause a significant decrease in cell viability even at the highest dose of 500 μg/mL. The ATP synthase activity of CCD-18Co was significantly diminished in the presence of PEO-IONPs but not GM3-IONPs. PEO-IONPs also compromised the membrane integrity of CCD-18Co. In contrast, cells exposed to GM3-IONPs showed significantly different cell morphology, but with no apparent membrane damage. The interaction of PEO-IONPs or GM3-IONPs with CCD-18Co resulted in a substantial decrease in the intracellular GSH levels in a time- and concentration-dependent manner. Conversely, levels of DHR-123 increased with IONP concentrations. Levels of caspase 3/7 proteins were found to be significantly elevated in cells exposed to PEO-IONPs. Based on the results, we assume GM3-IONPs to be biocompatible with CCD-18Co and could be further evaluated for selective killing of pathogens in vivo.